Comparing human coding to two natural language processing algorithms in aspirations of people affected by Duchenne Muscular Dystrophy - Schwartz, Carolyn E.; Stark, Roland B.; Biletch, Elijah; Stuart, Richard B.B. (Journal of methods and measurement in the social sciences, 2022)
Qualitative methods can enhance our understanding of constructs that have not been well portrayed and enable nuanced depiction of experience from study participants who have not been broadly studied. However, qualitative data require time and effort to train raters to achieve validity and reliability. This study compares recent advances in Natural Language Processing (NLP) models with human coding. This web-based study (N=1,253; 3,046 free-text entries, averaging 64 characters per entry) included people with Duchenne Muscular Dystrophy (DMD), their siblings, and a representative comparison group. Human raters (n=6) were trained over multiple sessions in content analysis as per a comprehensive codebook. Three prompts addressed distinct aspects of participants’ aspirations. Unsupervised NLP was implemented using Latent Dirichlet Allocation (LDA), which extracts latent topics across all the free-text entries. Supervised NLP was done using a Bidirectional Encoder Representations from Transformers (BERT) model, which requires training the algorithm to recognize relevant human-coded themes across free-text entries. We compared the human-, LDA-, and BERT-coded themes. Study sample contained 286 people with DMD, 355 DMD siblings, and 997 comparison participants, age 8-69. Human coders generated 95 codes across the three prompts and had an average inter-rater reliability (Fleiss’s kappa) of 0.77, with minimal rater-effect (pseudo R2=4%). Compared to human coders, LDA does not yield easily interpretable themes. BERT correctly classified only 61-70% of the validation set. LDA and BERT required technical expertise to program and took approximately 1.15 minutes per open-text entry, compared to 1.18 minutes for human raters including training time. LDA and BERT provide potentially viable approaches to analyzing large-scale qualitative data, but both have limitations. When text entries are short, LDA yields latent topics that are hard to interpret. BERT accurately identified only about two thirds of new statements. Humans provided reliable and cost-effective coding in the web-based context. The upfront training enables BERT to process enormous quantities of text data in future work, which should examine NLP’s predictive accuracy given different quantities of training data.